Enhanced Catalytic Activity of Immobilized Phytase into Polyvinyl Alcohol-Sodium Alginate Based Electrospun Nanofibers - Kamaci, Umran Duru; Peksel, Aysegul (SPRINGER, 2021)
Phytase was partially purified from cowpea seeds and it was successfully immobilized into polyvinyl alcohol-sodium alginate (PVA-SA) electrospun nanofiber. Electrospun nanofibers were fabricated by mixing PVA and SA at an 80:20 ratio. Also, they were obtained at a constant voltage (23 kV) and distance (14 cm), and different enzyme concentrations (0.5-2.0%) and flow rates (0.1-0.5 mL h(-1)). The characterization of the PVA-SA based nanofibers was carried out SEM, XRD, FT-IR, TG, and DSC techniques. The fiber diameter of the electrospun nanofibers was determined around 32 nm, and enzyme immobilization had no significant effect on the fiber diameter. The optimum temperature and pH value, different metal ions and additives effects on the catalytic activity of the free and immobilized phytase were also studied. The optimum pH and temperature results showed that the catalytic activity of phytase was enhanced after enzyme immobilization into PVA-SA based nanofibers compared to the free phytase.
Keywords: Sodium alginate; Nanofibers; Phytase; Electrospinning; Enzyme immobilization; COMPOSITE NANOFIBERS; PERFORMANCE; FABRICATION; LACCASE; ENZYME; Chemistry